Kebijakan Non Penal Dalam Pencegahan Tindak Pidana Perdagangan Telur Penyu Sebagai Satwa Yang Dilindungi di Kabupaten Bangka Tengah - Febbi Amalia; Dwi Haryadi; Rio Armanda Agustian (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
Non-penal policies in the prevention of the crime of trafficking in turtle eggs as protected animals are efforts used to overcome the occurrence of turtle egg trafficking by the community without using criminal punishment by focusing on prevention and coaching the community. Therefore, the purpose of this study is to find out what non-penal policies are implemented by the Directorate of Water and Air Police (DitPolairud) of the Babel Police and the Natural Resources Conservation Center (BKSDA) of the Bangka Conservation Resort in preventing the occurrence of the crime of trafficking turtle eggs as protected animals in Bangka Tengah Regency. This type of research is empirical juridical using a legal sociology approach. The formulation of the problem of this study is how to implement non-penal policies in the prevention of the crime of trafficking in turtle eggs as protected animals in Bangka Tengah Regency and how to overcome obstacles in implementing non-penal policies in the prevention of the crime of trafficking in turtle eggs in Bangka Tengah Regency. The results of this study are first, non-penal policies are implemented in the form of legal socialization, patrols, supervision and control around coastal areas, reprimands, and programs for the formation of supervisory community groups (POKMASWAS). The two efforts carried out in overcoming the obstacles that occurred were cooperation between the Directorate of Water and Air Police (DitPolairud) of the Babel Police and the Natural Resources Conservation Center (BKSDA) of the Bangka conservation resort and other agencies, socialization, appeals, patrols, recruiting cadres, and the development of alternative economies for the community.